Acquired protective immune response in a fish-myxozoan model encompasses specific antibodies and inflammation resolution. Issue 90 (July 2019) - Picard-Sánchez, Amparo; Estensoro, Itziar; del Pozo, Raquel; Piazzon, M. Carla; Palenzuela, Oswaldo; Sitjà-Bobadilla, Ariadna
Abstract: The myxozoan parasite Enteromyxum leei causes chronic enteritis in gilthead sea bream (GSB, Sparus aurata ) leading to intestinal dysfunction. Two trials were performed in which GSB that had survived a previous infection with E. leei (SUR), and naïve GSB (NAI), were exposed to water effluent containing parasite stages. Humoral factors (total IgM and IgT, specific anti- E . leei IgM, total serum peroxidases), histopathology and gene expression were analysed. Results showed that SUR maintained high levels of specific anti- E. leei IgM (up to 16 months), expressed high levels of immunoglobulins at the intestinal mucosa, particularly the soluble forms, and were resistant to re-infection. Their acquired-type response was complemented by other immune effectors locally and systemically, like cell cytotoxicity (high granzyme A expression), complement activity (high c3 and fucolectin expression), and serum peroxidases. In contrast to NAI, SUR displayed a post-inflammatory phenotype in the intestine and head kidney, characteristic of inflammation resolution (low il1β, high il10 and low hsp90α expression). Graphical abstract: Image 1 Highlights: Resistance to E. leei in re-exposed fish lasts up to 16 months. Specific antibodies (IgM) have a protective role for re-exposed fish at early times. Re-exposed fish show inflammatory resolution phenotype in intestine and head kidney. Cell cytotoxicity, peroxidases, and complement contribute to acquired resistance.